DESIGNING PUZZLE GAME TO INTRODUCE INDONESIA CULTURE USING UNITY 2020.3.16F1 - Tony Wibowo; Ricky Verniando (Universitas Internasional Batam, 2022)
In this era of time, information provided to the public regarding Indonesian culture is obtained from social media, website, books or brochures, while the information sources on these media only contain information in the form of picture, text and music. Puzzle game is a type of game that gives information in virtual way and interactive way. In this study, we will design and develop a puzzle game to introduce Indonesia culture using unity 2020.3.16f1. The result is released publicly. Effectiveness of the application need further study to validate.